Komitmen Kerja Pegawai Dinas Pendidikan Pemuda dan Olahraga Kota Pariaman - Tessa Melinda; Syahril Syahril (Universitas Negeri Padang, 2020)
The purpose of this research is to see the work commitment employee Dinas Pendidikan Pemuda dan Olahraga Kota Pariaman. The population of research was 55 people. The number of samples of research was 55 people. The research instrument was a questionnaire in the form Likert Scale which five choices of answer that has been tested for validity and reliability using the SPSS 16.0 version. Based on the research (1) the work commitment of employee identification is in a good enough category with in an average score of 76,91%, (2) the work commitment of employee involvement is in a good category with a score an average 81,23%, (3) the work commitment of employee trust is in a good enough category with a score an average 78,98%,(4) the work commitment of employee loyality is in a good category with a score an average 81,91%, (5) the work commitment of identification is in a good category with a score an average 81,36%, Overall, the work commitment employee Dinas Pendidikan Pemuda dan Olahraga Kota Pariaman was in a good category with an average of 80.08%.